2016
DOI: 10.1097/bpo.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of AVN Following Reconstructive Hip Surgery in Children With Cerebral Palsy

Abstract: Children with CP undergoing reconstructive hip surgery are at risk of developing AVN. Frequency and severity of this complication is poorly documented in the literature. On the basis of current evidence no significant risk factors were identified; however, it is not possible to draw firm conclusions about them. Incidence of AVN was higher in studies in which AVN was a primary outcome suggesting that the true frequency of AVN may be higher than is currently understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…While an additional procedure, epipihysiodesis can easily be combined with hardware removal and has minimal postoperative restrictions. Our rate of AVN (14.7%) compares with previously reported rates of 0 to 69% 14,26–28. Phillips et al26 demonstrated that large changes in MP and NSA were predictors of development of AVN.…”
Section: Discussionsupporting
confidence: 75%
“…While an additional procedure, epipihysiodesis can easily be combined with hardware removal and has minimal postoperative restrictions. Our rate of AVN (14.7%) compares with previously reported rates of 0 to 69% 14,26–28. Phillips et al26 demonstrated that large changes in MP and NSA were predictors of development of AVN.…”
Section: Discussionsupporting
confidence: 75%
“…The reported rate of postoperative complications after hip reconstructions varies considerably, from 0% to 81% (Ruzbarsky et al 2013). In a systematic review (Hesketh et al 2016), the AVN rate varied from 0% to 46%. These rates are difficult to compare because different classifications were used and because of mixed populations of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of AVN of the femoral head in children with CP after hip reconstruction is in the range of 0% to 69%. 10 , 11 , 13 , 18 , 20 , 28 - 30 A recent systematic review 31 on the subject revealed that most authors simply comment on the presence or absence of AVN in their complications, without further detail. Interestingly, the reported rates in our study as well as three others where AVN was the primary outcome measure are among the highest within the literature at 27% to 69%.…”
Section: Discussionmentioning
confidence: 99%